Revisiting the business English courses to meet the stakeholder's’ demand - Titien Indrianti (Jurnal Linguistik Terapan, 2019)
In the international business communication, English has become a medium of communication. To respond to such a global challenge, it is vital to equip students with Business English courses to prepare them to be more competitive worldwide. Nevertheless, studying Business English is quite problematic to many non-native learners since they have to focus both on the subject matter and the language. The present study is conducted to investigate the perspectives of the students and alumni on the Business English courses at the Business Administration Department, State Polytechnic of Malang. A survey on the second-year students and the alumni was conducted. The questionnaires were distributed to elicit their views on the courses, as well as their recommendations. The existing English syllabuses and materials were collected to be overviewed. The findings indicate most students are in favor of the course. Their motivation and interest in the course are good that they make some attempts to support their Business English skills acquisition. The business English competences, like: business presentation, business meeting, business socializing, negotiation, business correspondence, and knowledge, like global business issues are of their benefits to prepare them to work and develop their career in the future. The alumni claim they apply the Business English knowledge and skills in their workplace. However, the level of the application is different following their job position in the workplace. The students’ proposals for the course are that it should be presented in a more fascinating way and business communication skills are more emphasized. Besides, global business materials and vocabulary in business are to be more inserted. The alumni recommend providing more business communication practices and vocabulary enrichment. Showing the formal and informal English usage is also necessary. Besides, character building related to business needs to be inserted. The Business English syllabuses and materials were in line with the students’ and alumni’s expectation. The content and materials have already covered business knowledge and skills as expected by the stakeholder.